Using manure as fertilizer for maize could improve sustainability of milk production - Jiménez-Calderón, José D.; Martínez-Fernández, Adela; Prospero-Bernal, Fernando; Velarde-Guillén, José; Arriaga-Jordán, Carlos M.; Vicente, Fernando (Spanish Journal of Agricultural Research, 2018)
This study evaluated the effect of organic or chemical fertilization of maize on cow performance, economic outcomes, and greenhouse gas emission. Each type of maize silage according its different fertilization was used in two rations offered to two different groups of nine Friesian-Holstein cows throughout 4 months. The production cost of the maize silage was 8.8% lower for organic than for chemical fertilization. Both silages had similar nutritive value, except a higher concentration of starch in maize with organic fertilization, which allowed a reduction in the proportion of concentrate in the ration, saving 25.3 eurocents per cow in the daily ration, generating a positive balance of 21.8 eurocents per cow and day. The milk yield and composition were unaffected depending on the type of fertilization, whereas the estimation of CH4 and N2O emissions with chemical fertilization was higher than emissions with organic fertilization. As a result, it is possible to increase the sustainability and profitability of dairy production with reuse and recycling of manure.